2002
DOI: 10.1111/0033-0124.00328
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Time Back In: A Study on the Influence of Travel Time Variations and Facility Opening Hours on Individual Accessibility

Abstract: Although recent studies of individual accessibility have used detailed representations of urban street networks, unrealistic measures of travel time based on assumptions about constant travel speeds through the network were often used. Utilizing constant travel times does not allow for daily congestion and assumes that the effects of congestion are uniform throughout the city and affect all people equally. This research measures individual space-time accessibility in order to show that the incorporation of loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
115
0
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(123 citation statements)
references
References 47 publications
0
115
0
8
Order By: Relevance
“…Even for active travel, this influence still holds (Manaugh & El-Geneidy, 2011), as although the home to work distance is the major barrier to active commuting, the workplace is an origin for several other daily trips (Dong, Ma, & Broach, 2015), and its built environment features might impede or encourage the making of these trips by walking or cycling (Adams, Bull, & Foster, 2016). The uncertain geographical context problem (Kwan, 2012) gives further support to the importance of destinations in explaining travel behavior, since spatiotemporal variability is extremely important in understanding the real exposure of an individual throughout the day, not only to air pollution and associated health risks (Park & Kwan, 2017), but also to different space-time accessibility conditions (Miller, 2007;Weber & Kwan, 2002), which might exert a strong influence on mode choice and associated travel behavior.…”
Section: Different Destination Different Commuting Pattern? Analyzinmentioning
confidence: 99%
“…Even for active travel, this influence still holds (Manaugh & El-Geneidy, 2011), as although the home to work distance is the major barrier to active commuting, the workplace is an origin for several other daily trips (Dong, Ma, & Broach, 2015), and its built environment features might impede or encourage the making of these trips by walking or cycling (Adams, Bull, & Foster, 2016). The uncertain geographical context problem (Kwan, 2012) gives further support to the importance of destinations in explaining travel behavior, since spatiotemporal variability is extremely important in understanding the real exposure of an individual throughout the day, not only to air pollution and associated health risks (Park & Kwan, 2017), but also to different space-time accessibility conditions (Miller, 2007;Weber & Kwan, 2002), which might exert a strong influence on mode choice and associated travel behavior.…”
Section: Different Destination Different Commuting Pattern? Analyzinmentioning
confidence: 99%
“…The location preferences largely depend on income and housing budget, proximity to good schools and shopping centres ( Chiang and Hsu, 2005 ). Besides the consideration of distance in predicting accessibility to shopping centres and buying behaviour, time is another important factor that determines the shopping behaviour of urban consumers ( Weber and Kwan, 2002 ). Motivations of shopping in the street markets include inside and outside ambience, layout and extent of involvement of vendors in the selling process.…”
Section: Routes To Market and Shopping Behaviourmentioning
confidence: 99%
“…Within the STAM tradition, at least three studies are important for evaluation of accessibility along the temporal dimension. Weber and Kwan (2002) While previous research has clearly foregrounded the ramifications of opening hours for individual accessibility, no attempt has been made thus far to explore the ways in which opening hours can be amended to achieve a higher accessibility of urban services. In what follows, we will extend accessibility research in this direction.…”
Section: Space-time Demands Opening Hours and Accessibilitymentioning
confidence: 99%
“…In particular, a large number of researchers have shown that individual accessibility is shaped by inter alia an individual's mandatory activity schedule, trip chaining behaviour and transport mode availability (see e.g. Weber and Kwan, 2002;Kim and Kwan, 2003;Kwan and Weber, 2008;Schwanen and De Jong, 2008;Neutens et al, 2010c, b;Neutens et al, 2010d). …”
Section: Introductionmentioning
confidence: 99%